RELIGIOUS MODERNIZATION OF UKRAINE IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESS - Коваль, І. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Analyzed the essence of the place and role of religious factors in the processes of political integration. Characterized practice of individual EU countries and found the realities of Ukrainian integration, and often, and the disintegration of the function of religious modernization. It was established that today we can state unequivocally only integrative function of religion, which is to merge the society around religious beliefs and associations of citizens in the various religious communities. It is noted that the issue of diversifying the functions of religion at the present stage remains controversial